Modification And Testing Of Four Axes Filament Winding Machine - M. R. M., Rejab; K., Kadirgama; M. M., Noor; M. S. M., Sani (2008)
Filament winding technology is one of the production methods in composite manufacturing technology. This paper describes the design of filament winding machine with the four axes of winding system. The current filament winding machine consists of two axes. Two axes were added to the existing design. Four axes are rotation of mandrel, the horizontal carriage, controls the pay-out eye angle and controls the radial carriage movement. Keywords: Filament winding, Four axes, Automated winding system.